Postpartum Contraception in Northern Tanzania: Patterns of Use, Relationship to Antenatal Intentions, and Impact of Antenatal Counseling. Issue 4 (December 2015) - Keogh, Sarah C.; Urassa, Mark; Kumogola, Yusufu; Kalongoji, Samwel; Kimaro, Daniel; Zaba, Basia
Abstract : In Tanzania, unmet need for contraception is high, particularly in the postpartum period. Contraceptive counseling during routine antenatal HIV testing could reach 97 percent of pregnant women with much‐needed information, but requires an understanding of postpartum contraceptive use and its relationship to antenatal intentions. We conducted a baseline survey of reproductive behavior among 5, 284 antenatal clients in Northern Tanzania, followed by an intervention offering contraceptive counseling to half the respondents. A follow‐up survey at 6–15 months postpartum examined patterns and determinants of postpartum contraceptive use, assessed their correspondence with antenatal intentions, and evaluated the impact of the intervention. Despite high loss to follow‐up, our findings indicate that condoms and hormonal methods had particular and distinct roles in the postpartum period, based on understandings of postpartum fertility. Antenatal intentions were poor predictors of postpartum reproductive behavior. Antenatal counseling had an effect on postpartum contraceptive intentions, but not on use. Different antenatal/contraceptive service integration models should be tested to determine how and when antenatal counseling can be most effective.